God's Sovereignty and Man's Free Will: A Soteriological Analysis of Romans 8:29–30, Ephesians 1:4–5, And 2 Timothy 1:9 - Andarias Pangngaroan (International Journal Labs, 2025)
This research explores the complex relationship between God's sovereignty and man's free will in the context of Christian salvation, focusing on biblical verses that address divine predestination and human responsibility. The central research problem examined is the apparent theological tension between passages affirming God's absolute sovereignty in salvation (Romans 8:29–30, Ephesians 1:4–5, 2 Timothy 1:9) and those emphasizing human responsibility and free choice. The objective of this study is to provide a comprehensive exegetical analysis of key biblical texts to determine how divine sovereignty and human free will be harmonized in Reformed theology, while exploring various alternative theological frameworks. Through rigorous grammatical-historical exegesis, discourse analysis, and comparative theological methodology, this research analyzes the original Greek texts, examines their historical-cultural contexts, and evaluates different interpretative traditions. The results demonstrate that God's sovereignty and human free will are not mutually exclusive concepts, but rather theological realities that operate within a divine mystery transcending human comprehension. Exegetical findings reveal that biblical texts consistently affirm both God's absolute sovereignty over salvation and genuine human responsibility to respond in faith. The grammatical analysis shows consistent use of aorist tenses, indicating God's decisive action while maintaining parallel affirmations of human agency and accountability. The practical implications include a deeper understanding of grace as the foundation of salvation, motivation for evangelism grounded in divine election rather than human manipulation, and a basis for the certainty of salvation that does not depend on human performance.